2003
DOI: 10.1074/jbc.m304791200
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Glycosylphosphatidylinositols of Toxoplasma gondii

Abstract: Toxoplasma gondii is a ubiquitous parasitic protozoan, which causes congenital infectious diseases as well as severe encephalitis, a major cause of death among immune-deficient persons, such as AIDS patients. T. gondii is normally controlled by the immune system of healthy individuals, leading to an asymptomatic infection. T. gondii triggers early cytokine production, which, to a certain extent, protects the host against replication of tachyzoites, the infective form of the parasite. Glycosylphosphatidylinosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(39 citation statements)
references
References 44 publications
2
32
0
3
Order By: Relevance
“…This receptor is required for recognition of glycosylphosphatidylinositol-mucin molecules expressed by Trypanosoma cruzi (55)(56)(57). Purified Toxoplasma glycosylphosphatidylinositol molecules have also been reported to stimulate macrophage TNF-␣ production (58), and it is possible that TLR2 could be involved in recognition of these molecules. Nevertheless, TLR2…”
Section: Discussionmentioning
confidence: 99%
“…This receptor is required for recognition of glycosylphosphatidylinositol-mucin molecules expressed by Trypanosoma cruzi (55)(56)(57). Purified Toxoplasma glycosylphosphatidylinositol molecules have also been reported to stimulate macrophage TNF-␣ production (58), and it is possible that TLR2 could be involved in recognition of these molecules. Nevertheless, TLR2…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical studies using Chinese hamster ovary cells co-transfected with TLR and NF-kB reporter plasmids have shown that Toxoplasma GPI molecules are recognized by TLR-4 [39,40]. Interestingly, core glycans and lipid moieties obtained from parasite GPI were recognized by both TLR-2 and TLR-4.…”
Section: The Tlr Ligands Of Toxoplasma and Other Protozoansmentioning
confidence: 99%
“…Nevertheless, little is known about the parasite molecules involved in this process. Previous studies have largely focused on glycosylphosphatidylinositols (GPIs) from T. gondii tachyzoites responsible for the induction of TNF-α in macrophages464748. In our study, MIC3 was shown for the first time to be the relevant parasite molecule responsible for TNF-α induction (Fig.…”
Section: Discussionmentioning
confidence: 73%